Retirement confidence and financial security among working women - Sabri, Mohamad Fazli; Abd Rahim, Husniyah; Othman, Mohamad Amim (Lambert Academic Publishing, 2015)
Planning for a comfortable retirement and providing for their families' future well-being are paramount for women. Accumulating assets has always been important; now, however, protecting that wealth and generating retirement income have emerged as critical objectives as well. Available evidence suggested that women are financially at risk. Studies have shown that women's vulnerability increases as they age. Many of those in the 40 and above age group have not completed tertiary education and have either opted out of the workforce to take care of family or have erratic work histories and therefore are not able to establish a stable pension fund or savings for old age. In Malaysia and in many countries around the world, women live longer than men but they tend to suffer more debilitating diseases as they grow older. As their husbands pass on, more and more women suffer from poverty and may have to depend heavily on their children. This book discussed the levels of financial security and retirement confidence of working women in public sectors. Following that, multidisciplinary factors predicting financial security and retirement confidence have also been determined.